Perkiraan harga saham pada Perusahaan Astra Internasional Tbk. menggunakan metode moving average - Murfadiah, Elsa; Putra Hafiz, Ahsan; Mubarak, Fadhlul (e-Journal Perdagangan Industri dan Moneter, 2023)
This study uses a quantitative research method that aims to apply time series charts to the shares of PT Astra International Tbk. The right guess is the main information needed by investors in determining the next strategy in investing, which is Exponential Moving Average method. This method is a time series method used to predict the future using historical data. Giving weights involves a period, so the longer the period we use, the less weighting the last value we use. With the abundance of existing data, a system that utilizes past data has been built, in other words, a time series model tries to use the past time series to predict, later the system will be useful to assist investors in predicting estimates of the value of the Equity Fund in the future. so as to determine the right strategy for investment.